Application of Whole Exome Sequencing to Identify Disease-Causing Variants in Inherited Human Diseases - Gerald Goh; Murim Choi (Genomics & Informatics)
The recent advent of next-generation sequencing technologies has dramatically changed the nature of biomedical research. Human genetics is no exception-it has never been easier to interrogate human patient genomes at the nucleotide level to identify disease-associated variants. To further facilitate the efficiency of this approach, whole exome sequencing (WES) was first developed in 2009. Over the past three years, multiple groups have demonstrated the power of WES through robust disease-associated variant discoveries across a diverse spectrum of human diseases. Here, we review the application of WES to different types of inherited human diseases and discuss analytical challenges and possible solutions, with the aim of providing a practical guide for the effective use of this technology.